2008
DOI: 10.1002/anie.200802480
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Asymmetric Allylic Substitutions—Very High Regioselectivity and Air Stability with a Catalyst Derived from Dibenzo[a,e]cyclooctatetraene and a Phosphoramidite

Abstract: Transition-metal-catalyzed asymmetric allylic substitutions are widely employed. Steric course and regioselectivity of these reactions vary considerably, depending on the metal ion, ligands, the nucleophile, and the leaving group. Today, Pd catalysts [1] are usually employed for 1,3-disubstituted allylic substrates, while Ir catalysts [2] serve well for a broad range of monosubstituted allylic substrates.The currently best Ir catalysts are prepared from [{Ir-(cod)Cl} 2 ] (cod = cycloocta-1,5-diene) and a chir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(62 citation statements)
references
References 15 publications
1
56
0
5
Order By: Relevance
“…[285] Auch eine salzfreie Methode wurde entwickelt. [286] Des Weiteren wurden Phosphoramidite mit einer Amidgruppe eingesetzt, allerdings lieferten die Katalysatoren mit diesen Liganden nicht so hohe Enantioselektivitäten wie die zuvor genannten Katalysatoren.…”
Section: Mechanistische Untersuchungenunclassified
“…[285] Auch eine salzfreie Methode wurde entwickelt. [286] Des Weiteren wurden Phosphoramidite mit einer Amidgruppe eingesetzt, allerdings lieferten die Katalysatoren mit diesen Liganden nicht so hohe Enantioselektivitäten wie die zuvor genannten Katalysatoren.…”
Section: Mechanistische Untersuchungenunclassified
“…Resting state of the allylic substitution upon use of an in situ catalyst: Some time ago we have shown [4] that treatment of in situ generated K2 with weak acids, for example acetic acid, effects the reformation of K1. Now we have found that reformation of K1 also proceeds with allylic substrates and that the catalytically inactive complex K1 constitutes the resting state of the allylic substitution.…”
Section: Resting States and (P-allyl)ir Complexesmentioning
confidence: 99%
“…Both K1 and K2 have been previously described. [4] Addition of an allylic substrate to the solution of K2 rapidly led to reformation of the complex K1. As examples, reactions with cinnamyl acetate (C) and cinnamyl diethyl phosphate (D) are illustrated by 31 P NMR spectra in Figure 1.…”
Section: Resting States and (P-allyl)ir Complexesmentioning
confidence: 99%
See 2 more Smart Citations